If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-18-6k=-3(1-3k)
We simplify the equation to the form, which is simple to understand
-18-6k=-3(1-3k)
Reorder the terms in parentheses
-18-6k=+(-3+9k)
Remove unnecessary parentheses
-18-6k=-3+9k
We move all terms containing k to the left and all other terms to the right.
-6k-9k=-3+18
We simplify left and right side of the equation.
-15k=+15
We divide both sides of the equation by -15 to get k.
k=-1
| [x]-6=12 | | (5x+2)3= | | 1.5(x+8)=4.3+0.8x | | 10a-a= | | 18c-29c=151-30 | | 0.6x+1.5=-0.6(2x+5) | | 5(3x-1)+2x+9(2x-3)=5(6x-7)+11x-21 | | 4(-x-2)= | | 19-7p=-8p-(p-7) | | (7p-7)=10(2p+6)-7(-2+2p) | | 5x^4-8x^3-20x^2-4x+3=0 | | -6y+3x=-39 | | 4(y+2)-2(1-y)-4y=0 | | -33=2+5y | | 7(-2y+3)= | | 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 | | 4x-3+3=12 | | 9x-7=4x+9 | | 3x^2-5x+5=33 | | 10x-35+3x=5x-7a | | N+11=2 | | 2(3+x)=14x | | 11(4-3x)-5(2x+13)=194 | | -2y-42=-4(y+7) |